Le laboratoire de François Gros au Collège de France - Lazar, Monique (Comptes Rendus Biologies)
I was recruited by François Gros as a PhD student in his laboratory at the Institut de Biologie Physico-Chimique in 1965, and continued to work with him after I graduated. In 1973, when he was appointed Professor of Cellular Biochemistry at the Collège de France, François decided to set up a team working on neuronal differentiation. He asked me to take part in this new scientific adventure. Here I’d like to talk about the members of his laboratory and some of their scientific work, in particular that on the cytoskeleton of neurons.